1978
DOI: 10.1083/jcb.79.2.573
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome movement in lysed mitotic cells is inhibited by vanadate.

Abstract: Mitotic PtK1 cells, lysed at anaphase into a carbowax 20 M Brij 58 solution, continue to move chromosomes toward the spindle poles and to move the spindle poles apart at 50% in vivo rates for 10 min. Chromosome movements can be blocked by adding metabolic inhibitors to the lysis medium and inhibition of movement can be reversed by adding ATP to the medium. Vanadate at micromolar levels reversibly inhibits dynein ATPase activity and movement of demembranated flagella and cilia. It does not affect glycerinated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(93 citation statements)
references
References 3 publications
6
87
0
Order By: Relevance
“…A and F were taken before lysis; B and G, 1 min after lysis ; C and H, 2 min after lysis ; D and 1, 4 min after lysis ; and E and 1, 6 min after lysis . Bar,5 ,um . and cytochalasin B, but in 10 mM ATP and in NEM-S,, furrow diameter increased slowly and relaxation often did not occur until several minutes after lysis. These observations suggest that cytochalasin B, alkaline pH, and high calcium act directly on the contractile ring to disorganize and relax the furrow, and that NEWS, and high ATP have an indirect effect on furrow integrity.…”
Section: Cleavage Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…A and F were taken before lysis; B and G, 1 min after lysis ; C and H, 2 min after lysis ; D and 1, 4 min after lysis ; and E and 1, 6 min after lysis . Bar,5 ,um . and cytochalasin B, but in 10 mM ATP and in NEM-S,, furrow diameter increased slowly and relaxation often did not occur until several minutes after lysis. These observations suggest that cytochalasin B, alkaline pH, and high calcium act directly on the contractile ring to disorganize and relax the furrow, and that NEWS, and high ATP have an indirect effect on furrow integrity.…”
Section: Cleavage Inhibitionmentioning
confidence: 99%
“…PtK, cells were used in all experiments and were maintained and handled for light microscopy as described previously (5). Coverslips were mounted on slides with coverslip fragments as spacers.…”
Section: Tissue Culture Cells and Cell Lysismentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of vanadate into lysed mitotic cells in the presence of EGTA to buffer the concentration of free Ca 2+ , caused only an impact on anaphase B [87,88], which was subsequently confirmed after inhibition of dynein ATPase activity with erythro-9-[3-(2-hydroxynonyl)] adenine [89]. Curiously, milimolar concentrations of vanadate or anti-dynein antibody injections did not affect anaphase movements in unlysed Ptk1 cells [90,91].…”
Section: Kinetochore Dyneinmentioning
confidence: 99%
“…These data indicated that in some systems, pulling forces acting on astral microtubules are the main drivers of spindle elongation, whereas spindle midzone microtubules resist or govern the rate of pole separation. Cytoplasmic dynein located at the cell cortex has been implicated in this astral MT pulling mechanism [89,90,96,[233][234][235]. On the other hand, proteins required for microtubule polymerization and growth/stabilization of interpolar microtubules [236], such as CLASPs [219], coordinated with the activity of kinesin-5 at the spindle midzone, might work as governors [237].…”
Section: Anaphase a Vs Anaphase Bmentioning
confidence: 99%